Promoting entrepreneurship in cultural and creative industries in Europe: creative industries entrepreneur’s network : the CINet project - Porfírio, José (2018)
CINet, the Creative Industries Network of Entrepreneurs was a project inspired in the unique ecology of Nottingham’s creative industry sector. The project was funded by the European Commission under Leonardo da Vinci Transfer of Innovation Program (cinet.eu.uab.pt) CINet brings together creative industry clusters in Nottingham, Greece, Portugal and Spain. Its aim was to facilitate shared learning amongst entrepreneurs and to promote entrepreneurship in the Cultural and Creative Industries (CCI) by developing the conditions for learning and collaborative advantage within small firm clusters. CINet Partners came from several southern European countries (Portugal, Spain, Greece and France), the UK and Romania. They were: • Universidade Aberta, Lisbon (Portugal) – Project Coordinator • UK WON (UK Work Organisation Network) • Universitat Oberta de Catalunya, Barcelona (Spain) • University of Piraeus Research Centre-UPRC, Athens (Greece) • Association for Education and Sustainable Development (Romania) • DNA, Cascais (Portugal) • Media Deals Association (France) CINet developed an acceleration program that was offered through three main modalities: full eLearning; blended-learning and full face-to-face training. This permitted to test the different conditions and respective advantages and drawbacks of training entrepreneurs. The outcomes of the project allowed the creation of a network of creative entrepreneurs between the three Southern European Countries involved; an improvement of knowledge concerning important differences deriving from the different type of entrepreneurship training delivery, and also the need to consider different cultural conditions when defining public policies and actions concerning entrepreneurship development in CCIs.